Using Cartoon Movie to Improve Speaking Skill - Suparta Rasyid (Research in English and Education Journal, 2017)
This study is aimed to find out whether the use of English cartoon movie can improve students’ achievement at second grade of SMU Abulyatama. The samples of this study were 20 students of class 2 IPA2. To collect the data, the writer utilized experimental design one group pre-test and post-test. The instrument used was oral test. The speaking aspects covered in this study were grammar, vocabulary, and pronunciation. The result shows that the students’ speaking score increased in all aspects. The grammar aspect noted the highest/significant increase because some of students’ achieved very low in grammar before using the movie in learning, but later the significant improvement is on the grammar aspect. It increased from 25 to 44 or 19 points. It explains that the English cartoon movie can be one of the good materials to improve students’ speaking skills, particularly in grammar aspect.